The Association between Maternal Adverse Childhood Experiences and Substances Abuse: A Systematic Review - Adriana, Nadya Puspita (GLOBAL HEALTH SCIENCE GROUP, 2024)
An increasing number of studies are identifying associations between adverse childhood experiences (ACEs) and substances abuse. We aimed to review the association between multiple types of ACE with different kind of substance abuse among pregnant women. This research aims to determine the relationship between mother children's problems experiences and substance use. Method: We looked through the databases at ProQuest, PubMed, and Science Direct databases were utilized by the authors to do an extensive and methodical search of the English-language literature for studies on adverse childhood events that were published until January 31, 2024. The search phrases used are “adverse childhood experiences”, “maternal”, and “substances abuse”.Results: Most of the article were cohort studies conducted in the USA. All studies assessed ACEs retrospectively. The main conclusions of the studies were that there is a a positive association between ACEs with the development and severity of substance use disorder among pregnant women. Conclusions: We found that adverse childhood experiences exposure can result in different kind of substances abuse among pregnant women compared with those without adverse childhood experiences.